Measuring the economic performance of mixed crop-livestock farming systems in Egypt: A non-parametric DEA approach - Osama Ahmed; Sameh Abdel-Salam; Supawat Rungsuriyawiboon (New Medit, 2020)
This study examines the relative technical efficiency of mixed crop-livestock farming systems and assesses their economic performance between the Upper and Delta regions of Egypt. A non-parametric data envelopment analysis (DEA) method is empirically applied for measuring technical efficiency using farm-level data for 838 mixed crop-livestock farmers. The findings show that the mixed crop-livestock farms in Egypt are operating at a low level of technical efficiency, indicating most farms are unable to catch up with the current production frontier and existing production technologies. Farms in the Delta region perform slightly better than those farms in Upper Egypt. Results also suggest that technical efficiency improvement is positively affected by farmers' education, having a farm milk production certificate, and being located in the Delta region, whereas farm size negatively affects the economic performance of mixed crop-livestock farming systems in Egypt.
Keywords: C14; D24; Q12; Q18; 330; technical efficiency; non-parametric DEA model; livestock products; farming systems in Egypt